Adaptive Sports Exposure Across Physical Medicine and Rehabilitation Residency and Sports Medicine Fellowship Programs: A National Cross-Sectional Website Analysis - Chantal Nguyen; Emily Moya; Mehul Chowdarapu; Durga Monica Ghosh; Miriam Agaibi; Jacob Nguyen; Molly Timmerman (American Journal of Physical Medicine & Rehabilitation, 2026)
Adaptive sports improve health and quality of life for people with disabilities, yet the extent of adaptive sports exposure in physical medicine and rehabilitation (PM&R) training is unclear. This cross-sectional study reviewed the public websites of 115 accredited physical medicine and rehabilitation residency programs and 26 sports medicine fellowship programs for any mention of adaptive sports, characterizing exposure type, target populations, and associated program characteristics. Adaptive sports were mentioned by 32 residency programs (27.8%) and 8 fellowship programs (30.8%). Mention varied significantly by geographic region in both cohorts (residency, West 64% vs. South 19%, P =.017; fellowship, Midwest 80% vs. South 0%, P =.035) and, among residencies, was associated with larger program size and a greater number of associated subspecialty fellowships. Residency exposure was predominantly volunteer-based, whereas fellowship exposure was exclusively clinical or undisclosed; target populations served were frequently unspecified. Programs have an opportunity to expand structured adaptive sports training and to clearly convey these opportunities to applicants and patients.